2014
DOI: 10.1097/yco.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

When time stands still

Abstract: PTSD development is associated with chronodisruption findings. Evaluation and treatment of sleep and circadian disruption should be the first steps in PTSD management. State-of-the-art methods of circadian rhythm assessment should be applied to bridge the gap between clinical significance and limited understanding of the relationship between traumatic stress, sleep and circadian system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 153 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…Circadian dysregulation and sleep disturbances represent a core feature of traumaticstress-related disorders, often closely related to the severity of PTSD psychopathology [211][212][213]. Circadian dysregulation after traumatic stress can lead to a breakdown of biological adaptive mechanisms and may constitute another crucial link between traumatic stress and OXS [214,215].…”
Section: Circadian Dysregulation and Melatoninmentioning
confidence: 99%
“…Circadian dysregulation and sleep disturbances represent a core feature of traumaticstress-related disorders, often closely related to the severity of PTSD psychopathology [211][212][213]. Circadian dysregulation after traumatic stress can lead to a breakdown of biological adaptive mechanisms and may constitute another crucial link between traumatic stress and OXS [214,215].…”
Section: Circadian Dysregulation and Melatoninmentioning
confidence: 99%
“…Moreover, Voigt et al reported that circadian disorganization disrupts the composition of the intestinal microbiota ( Voigt et al, 2014 ). Emerging evidence strongly indicates notable links between circadian rhythm disturbances and mental health conditions, such as PTSD ( Agorastos et al, 2014 ; Olff et al, 2019 ). Furthermore, researchers have initiated investigations into the interplay between the circadian system and mental health ( Walker 2nd et al, 2020 ).…”
Section: The Microbiota-gut-brain Axismentioning
confidence: 99%
“…Relevant preclinical and clinical literature has neglected the potentially important pathophysiological role of circadian rhythm disruption in PTSD (26). Despite considerable research examining the association between sleep and PTSD (27), few studies have attempted to identify specific underlying biological/circadian mechanisms that may account for this relationship (28, 29).…”
Section: Introductionmentioning
confidence: 99%
“…McFarlane et al (30) found lower urinary melatonin levels after trauma exposure, predicting a higher risk for PTSD, while van Liempt et al (31) reported undisturbed nocturnal plasma melatonin profiles in PTSD patients. Other evidence underscores a key function of the melatonergic system in sleep and chronodisruption following trauma exposure and its probable role in a chronically dysregulated circadian network in PTSD (26, 32).…”
Section: Introductionmentioning
confidence: 99%